Phytomedical investigation of Najas minor All. in the view of the chemical constituents - Topuzović, Marina D.; Radojević, Ivana D.; Dekić, Milan S.; Radulović, Niko S.; Vasić, Sava M.; Čomić´, Ljiljana R.; Ličina, Braho Z. (Technische Universität Dortmund, 2015)
Plants are an abundant natural source of effective antibiotic compounds. Phytomedical investigations of certain plants haven’t still been conducted. One of them is Najas minor (N. minor), an aquatic plant with confirmed allelopathy. Research conducted in this study showed the influence of water and ethyl acetate extracts of N. minor on microorganisms, in the view of chemical profiling of volatile constituents and the concentrations of total phenols, flavonoids and tannins. Antimicrobial activity was defined by determining minimum inhibitory and minimum microbicidal concentrations using microdilution method. Influence on bacterial biofilm formation was performed by tissue culture plate method. The total phenolics, flavonoids and condensed tannins were determined by Folin-Ciocalteu, aluminum chloride and butanol-HCl colorimetric methods. Chemical profiling of volatile constituents was investigated by GC and GC-MS. Water extract didn't have antimicrobial activity below 5000 µg/mL. Ethyl acetate extract has shown strong antimicrobial activity on G+ bacteria - Staphylococcus aureus PMFKGB12 and Bacillus subtilis (MIC < 78.13 µg/mL). The best antibiofilm activity was obtained on Escherichia coli ATCC25922 (BIC50 at 719 µg/mL). Water extract had higher yield. Ethyl acetate extract had a significantly greater amount of total phenolics, flavonoids and tannins. As major constituent hexahydrofarnesyl acetone was identified. The ethyl acetate extract effected only G+ bacteria, but the biofilm formation of G-bacteria was suppressed. There was a connection between those in vivo and in vitro effects against pathogenic bacterial biofilm formation. All of this points to a so far unexplored potential of N. minor.
EXCLI Journal ; Vol. 14, 2015
Keywords: Najas minor; antimicrobial; antibiofilm; total phenolic content; flavonoid and tannin content; volatile constituents; 610